Prevalence and outcome of care among patients with spinal cord injury in a Nigerian Tertiary Health Institution - Olufemi O. Oyediran, Dr., PhD (Elsevier, 2022)
Objective: This study assessed the prevalence, causes, pattern of management and outcome of care among patients SCI in University College Hospital, Ibadan, Nigeria. Methods: The study adopted a retrospective research design and case files of all patients with spinal cord injury that received treatment at the hospital from 2015 to 2018 were used for the study. A self-developed checklist was used for data collection. Collected data were analysed using the statistical package for the social sciences (SPSS) version 25. The data were presented with descriptive and inferential statistics at a significance level of p = 0.05. Results: Findings showed that 132 admitted patients out of a total of 850 admissions over four years had SCI with a prevalence rate of 15.5% with highest percentage in 2018 and 65.2% of the SCI resulted from trauma and 34.8% were non-traumatic. Majority of the patients (99.2%) were given analgesics, 97.7% were placed on bed resting, 90.2% received psychotherapy, 89.4% were placed on adequate nutrition, 71.2% were placed on anticoagulants 68.2% placed on catheterization and 57.6% benefited from surgery. Findings also showed that outcomes of care for spinal cord injury ranges from Paraplegia (29.5%), salvaging of bladder or bowel continence (25.0%) and Quadriplegia (15.2%). Conclusion: The study concluded that there is high prevalence of SCI and trauma, road traffic accident and occupational hazard were the major causes of spinal cord injury.